A guide to post-mortem examination procedure in mouse models. (October 2022) - Rodrigues, Alexandra; Beresford, Lynn; Scudamore, Cheryl L; Yon, Marianne
The main objective of a post mortem is to identify, at a macroscopic level, any anatomical features that characterise mutant or sick mice and to describe lesions contributing to morbidity and mortality. Tissues collected for subsequent examination require appropriate handling and preservation to prevent deterioration. Therefore, efficient routine procedures are essential to facilitate histology and to ensure high-quality samples. In addition, optimised techniques minimise data loss from damaged samples reducing the numbers of animals used and supporting the 3Rs principle of reduction. Here, we describe an optimised method for tissue collection in the mouse. Training tips and points for caution are included.